Quality of life among elderly population in an urban slum of Tirupati city - Guthi, Visweswara Rao; Prathyusha, Tirupati Venkata Devi; Kondagunta, Nagaraj; Kavyasree, Nakkala; Kavitha, Chimmata; Kavitha, Mandapalli (International Journal Of Community Medicine And Public Health, 2019)
Background: Healthy aging is a process of developing and maintaining the functional ability that enables well- being in older age. Objective of the present study is to assess the quality of life among elderly population using WHOQOL-BREF scale and to determine the association between socio demographic factors and quality of life. Methods: Community based cross- sectional study was conducted in the urban field practice areas of SVIMS-Sri Padmavathi Medical College for women, Tirupati for a period of one month (February 2019 to March 2019). Study population were Elderly of age 60 years and above. Total 60 elderly were included in the study. Quality of life was assessed using WHOQOL-BREF questionnaire. Results: Most of the study population was in the age group of 60-64 years, Most of them were females (71.7%). More than one third were illiterates (36.7%), 30% were studied up to primary school. 93.3% of study population were suffered from some form of illness. Mean total transformed score was high among ≥70 years compared to <70 years, Males were showing high mean total transformed score compared to females, literates were showing high score and persons with illness were showing high scores and persons without illness. Conclusions: It is concluded from this study that most of the elderly population are suffered from some form of illness. Overall quality of life is good among elderly within 70 years of age, males, literates and who are in living as married compared to their counter parts.